Az adóráták és a korrupció hatása az adóbevételekre - nemzetközi összehasonlítás: OECD országok, 2000 - 2004 - Mária Lackó (Hungarian Academy of Sciences, Institute of Economics, 2008)
– The paper exemines the combined effect of the statutory tax rates (especially tax rates on labor) and the level of corruption on the variation of relative tax revenues (their ratio to GDP) in the OECD countries in 2000-2004. The relationship between the interaction of tax rates with corruption and the relative tax revenues shows an inverse U-shape line, as if it were a Laffer-curve. However, according to our econometric analysis, this relationship is the outcome of several separate effects: the first is a direct positive effect of the tax rates on relative tax revenues, the second is a negative effect of the interaction between the tax rates and the level of corruption, and the third one is a negative effect of the interaction between the tax rates and the level of underdevelopment. This means that higher tax rates go together with higher relative tax revenues, but in each country the extent of this effect is modified by further factors: the higher the level of corruption and the more the country is underdeveloped, the less is the effect of tax rates toward increasing the relative tax reveneues. The econometric results allow us to calculate the shortfalls of tax revenues due to the interaction variables (tax rates with corruption and with underdevelopment). These shortfalls of tax revenues (in percent of GDP) can be seen as indicators of the size of the hidden economy. The size of the shortfall of tax revenues in Hungary in 2004 reaches 7 percent of the GDP. Higher shortfalls are experienced in Turkey (8.4%) and Poland (8%), while in Greece, Slovakia, Italy and the Czech Republic the calculated tax-shortfalls are around 6%.
Keywords: J2; E26; H26; 330; taxation; corruption; hidden economy; Steuertarif; Korruption; Steuereinnahmen; Schattenwirtschaft; OECD-Staaten